2020
DOI: 10.1155/2020/4230627
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological Analysis of Floods in Ghana

Abstract: The first episodes of floods caused by heavy rainfall during the major rainy season in 2018 occurred in Accra (5.6°N and 0.17°W), a coastal town, and Kumasi (6.72°N and 1.6°W) in the forest region on the 18th and 28th of June, respectively. We applied the Weather Research and Forecasting (WRF) model to investigate and examine the meteorological dynamics, which resulted in the extreme rainfall and floods that caused 14 deaths, 34076 people being displaced with damaged properties, and economic loss estimated at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 38 publications
6
32
0
Order By: Relevance
“…During the last century Ghana has been challenged by severe floods affecting more than 3.5 million people and causing 567 losses of human lives (EM-DAT 2015). From 2015 to 2018 extreme rainfall events concurrent with the peak of the rainy season in the coastal metropolitan, caused 164 deaths and more than 43,000 people were displaced with damaged properties (Ansah et al 2020;Marrengane and Croese 2020). It can be reasonably anticipated that the citizens of Accra will experience an increase in urban flood frequency due to the projected increase of precipitation patterns with a 1.5 o C global warming (Klutse el al.…”
Section: Study Areamentioning
confidence: 99%
“…During the last century Ghana has been challenged by severe floods affecting more than 3.5 million people and causing 567 losses of human lives (EM-DAT 2015). From 2015 to 2018 extreme rainfall events concurrent with the peak of the rainy season in the coastal metropolitan, caused 164 deaths and more than 43,000 people were displaced with damaged properties (Ansah et al 2020;Marrengane and Croese 2020). It can be reasonably anticipated that the citizens of Accra will experience an increase in urban flood frequency due to the projected increase of precipitation patterns with a 1.5 o C global warming (Klutse el al.…”
Section: Study Areamentioning
confidence: 99%
“…Landslides resulting from a tropical storm usually lead to the disruption of transport activities with negative impact on economic activities. Many studies have reported about the impact of floods in West Africa (Schaer and Hanonou, 2017;Salack et al, 2018;Gbode et al, 2019;Ansah et al, 2020). Participants also highlighted that tropical storms via increased wave conditions have significant negative impact in the fishing sector including the destruction of small-size fishing boats and loss of lives, destruction of fishing infrastructure in coastal areas and disruption of fishing activities.…”
Section: Tropical Stormsmentioning
confidence: 99%
“…As a result, it is necessary for detailed statistical studies to be conducted with more emphasis on particular rainfall seasons. Aside from the rainfall trends and variations, many attempts have been made to understand different aspects of the climate system in Ghana which include the onset, cessation, and length of the rainfall seasons, rainfall and dry spell predictions, and temperature trend analysis [15][16][17][18][19]. Interestingly, the above studies have successfully explained the behaviors of temperatures, rainfall, dry spells at seasonal and sub-seasonal scales and their link to major meteorological parameters like seas surface temperatures (SST) and intertropical discontinuity.…”
Section: Introductionmentioning
confidence: 99%